Efektivitas Monitoring EWS Terintegrasi Berbasis Elektronik Terhadap Deteksi Risiko Mortality di RS Bendan Kota Pekalongan - Himawati,; Pohan, Vivi Yosafianti; Hartiti, Tri; Masrukhi,; Armiyati, Yunie (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to determine the effectiveness of an integrated electronic-based Early Warning Score (EWS), known as TeBar, compared with a paper-based EWS form in detecting mortality risk at Bendan Regional General Hospital, Pekalongan City. A quasi-experimental study with a pretest–posttest control group design was employed. The sample consisted of 60 inpatient ward nurses selected using purposive sampling. The inclusion criteria were staff nurses working in the Jlamprang and Truntum wards, while nurse managers and nurses on leave, permission, or ward transfer during the study period were excluded. The intervention involved monitoring patients using the electronic integrated EWS (TeBar) in the intervention group, whereas the control group used the conventional paper-based EWS form. Data were collected using web-based observation sheets. Statistical analysis was performed using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test. The results showed that before implementing the electronic EWS, most mortality risk detections in the intervention group were inaccurate (80%); however, after implementation, all detections were accurate (100%). In the control group, mortality risk detection using the paper-based EWS remained largely inaccurate both before (66.7%) and after (60%) the intervention. The Wilcoxon test revealed a significant difference in mortality risk detection before and after the use of the electronic EWS (TeBar) in the intervention group (p = 0.000), whereas no significant difference was found in the control group using the paper-based EWS (p = 0.346). Furthermore, the Mann–Whitney U test indicated a significant effect of electronic EWS (TeBar) monitoring on mortality risk detection compared to the paper-based EWS (p = 0.000). In conclusion, the electronic EWS (TeBar) is effective in detecting early mortality risk in inpatient wards at Bendan Regional General Hospital, Pekalongan. The use of electronic EWS improves the accuracy of clinical documentation, accelerates clinical decision-making, and enhances patient safety as part of efforts to improve the quality of nursing care.